The efficiency of millimeter-wave resonance therapy in cytotoxic supression of hemopoiesis - N. P. Kareva; T. I. Pospelova; S. V. Pozdnyakova; G. Yu. Ushakova; G. V. Shamayeva (Бюллетень сибирской медицины, 2008)
.